Principles of Entrepreneurship (ENT530): Business Model Canvas: Baggy Store Sdn Bhd (Easy-Go Laundry Bag) / Nur Syazwani Radzali ... [et al.] - Radzali, Nur Syazwani; Khairul Anwar, Farah Najwa; Ismail, Nur Amirah Atikah; Md Lailee, Siti Puteri Nur Edrina (2020)
Our company is called Baggy Store Sdn. Bhd focus on the product like bag and various types of bag but the main product that we focused on is laundry bag named easy-go laundry bag. The reason for us to focus on laundry bag is because we see the potential for our business to grow as this is the product that gets the most demand in the community. We are aware of a society where they need a laundry bag as a daily necessity at home. People out there want a laundry bag that has a lot of privileges that can fill a lot of dirty clothes. Easy-Go Laundry bag has little understanding of consumer segments, want and needs. We also find no longer in the market able to create a laundry bag that has a large capacity of space. Apart of that, we took this opportunity to produce a laundry bag named easy-go laundry bag that fullfil all the criteria desired by the community out there.